Relation between free testosterone levels and body composition in hemodialysis patients - Nourhan F. Awad; Salah S. Naga; Iman E. Elgohary; Nesrine M. EL Azhary; Sara T. Ibrahim (Alexandria Journal of Medicine)
Introduction Testosterone deficiency is common among hemodialysis (HD) patients. Numerous studies demonstrated a correlation between testosterone levels and body composition in the general population. However, this correlation was not thoroughly investigated in HD patients. Therefore, we conducted this study to assess the correlation between free testosterone levels and body composition in HD patients.Methods A total of 80 males were included in this study, compromising 40 hD males in addition to age-matched 40 healthy controls. Free testosterone levels and body composition were measured using the InBody device.Results Free testosterone level was significantly lower in the HD group (median; 75 pg/dl and interquartile range (IQR); 55.8–87.8 pg/dl) than in the control group (median; 101 pg/dl and IQR 82.8–115 pg/dl) with p = 0.004. The skeletal muscle index (SMI) was significantly lower in the HD group (median; 10.18 and IQ; 9.5–10.6) compared to the control group (median; 11.1 and IQR; 10.3–11.7), with p < 0.001. The lean tissue index (LTI) was significantly lower in the HD group (median; 18.44 and IQ; 17.3–19.3) than in the control group (median; 19.88 and IQ; 18.4–20.8), with p = 0.006. The free testosterone level demonstrated a positive correlation with SMI (r = 0.34, p = 0.03) and LTI (r = 0.33, p = 0.04).Conclusion There is a correlation between free testosterone levels and body composition in HD patients.